Just Code (Johns Hopkins University Press, 2026)
How code shapes power and inequality across technology, governance, and global political economies.Code—whether software routines, legal frameworks, or informal social norms—shapes the world around us in profound and often invisible ways. In Just Code, editors Jeffrey R. Yost and Gerardo Con Díaz bring together a diverse group of scholars to examine how different forms of code both structure and reinforce power dynamics across societies.From algorithmic bias in artificial intelligence to global labor practices, this collection uncovers the hidden mechanisms by which code perpetuates inequality and injustice. It explores connections among technology, governance, and socioeconomic systems to reveal how code is both a tool of control and a product of the power structures it enables. Contributors analyze topics such as platform economies, algorithmic collusion, and labor practices in the tech industry, as well as how systems of representation and communication encode biases that amplify racial, gendered, and economic inequalities. These essays provide a critical lens for understanding how code intersects with politics and global cultures of technology production and use.By broadening the concept of "code" to include legal, social, and cultural systems, this collection challenges readers to see beyond the technical and interrogate the structures of power embedded in every layer of modern life. Just Code introduces a new framework for understanding the relationships among information technologies, systemic inequities, and the political economies that sustain them.